Metode Bermain Peran di RA Muslim Medan Dalam Meningkatkan Empati Sosial Emosional Anak - Putri, Hairani Ananda; Nashfatih, Fadiah Dian; Marbun, Ika Holpiana Sari; Makhfiro, Nur Rizkiyah; Ibrahim NST, Nurul Fadilah (Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out how the use of role-playing methods can increase children's emotional empathy abilities at RA Muslim Medan. The role-playing method is used as a strategy to improve children's social-emotional abilities. The research results show that the use of role-playing methods can improve children's social-emotional empathy abilities. Children who take part in role-playing activities have better empathy abilities compared to children who do not take part in these activities